Need Assessment of Developing Android Application for English Learning in Digital Era - Purbasari, Rosalinda Ayu; Suryani, Nunuk; Ardianto, Deni Tri (Universitas Negeri Semarang, 2019)
This changing era demanded innovative strategy in all aspect, especially in education. This research was a need assessment which aimed to analyze the need of An-droid application for English learning in Senior High School in Magelang Regency, Central Java. To collect the data, interviewing English teachers and distributing the questionnaire to the students were conducted. Based on the result of the interview, as a facilitator, teachers needed assistants to assist the students in learning English. In this case, technology was needed. It was supported by the data that there were 82,5% students owned smartphone and 95% of them agreed that using Android application was more interesting. There was 63% of the students spent their time more than 6 hours per day with their smartphone. Thus , it could be concluded that nowadays, it is urgently needed to develop Android application to support English self assessed learning in this digital era. Abstrak Perubahan era menuntut adanya strategi yang inovatif di segala aspek kehidupan, terutama pendidikan. Penelitian ini merupakan penelitian pendahuluan yang bertujuan untuk menganalisa kebutuhan aplikasi Android untuk mendukung pembelajaran Bahasa Inggris di Sekolah Menengah Atas di Kabupaten Magelang, Jawa Tengah. Untuk mengumpulkan data, metode yang dilakukan adalah wawancara dengan guru Bahasa Inggris dan membagikan kuesioner kepada siswa. Dari hasil wawancara, disebutkan bahwa, sebagai fasilitator, guru membutuhkan asisten untuk memantau siswa dalam belajar secara mandiri. Oleh karena itu, peran teknologi dibutuhkan dalam hal ini. Data menunjukkan bahwa siswa yang memiliki smartphone berjumlah 82,5% dan 95% dari mereka setuju bahwa kegiatan belajar mandiri menggunakan aplikasi Android lebih menarik. Hal ini didukung dengan intensitas siswa dengan smartphone yaitu 63% dari mereka menghabiskan waktu lebih dari 6 jam sehari untuk berinteraksi menggunakan smartphone. Maka dari itu, di era digital seperti sekarang ini, aplikasi Android penting untuk dikembangkan guna mendukung pembelajaran Bahasa Inggris secara mandiri. Keywords: android application; educational technology, English learning, need assessment; self-assessed learning